Penguatan Profesionalisme Layanan Massage dan Refleksi Panggilan melalui Pelatihan Standarisasi Berbasis Etika dan Kenyamanan Konsumen - Sofia Daniati; Kuswidyaningrum Naharina J; Ani Tias Sinora; Jesicka Puspita Sari (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
This Community Service activity aims to strengthen the professionalism of mobile massage and reflexology services through service standardization training based on ethics and consumer comfort. The activity was conducted at the PGOT Mardi Utomo Social Service Institution in Semarang as part of a social rehabilitation program to enhance the skills and work readiness of the beneficiaries. The implementation methods included lectures, interactive discussions, and practical demonstrations focusing on service standards, professional ethics, service communication, as well as consumer safety and comfort aspects. The results indicate an improvement in participants’ understanding of the importance of service quality that is not only oriented toward technical skills but also toward professional attitudes and ethical conduct in service delivery. Participants were able to identify fundamental principles of professional service and apply them in simulated practice. This activity contributes to shaping participants’ professional attitudes as service providers and supports empowerment and socio-economic independence of the beneficiaries.